Clinical, Imaging and Anatomopathological Characterization of Focal Liver Lesions - Emma Midiannys Fonte Griñán; Maribel Misas Menéndez; Ileana González Santana (Medisur)
Background: abdominal ultrasound is essential for the accurate diagnosis of focal liver lesions. Benign or malignant tumors are commonly detected by this test, although confirmation is completed with clinical signs and biopsy results. Objective: to analyze the relationship between clinical, imaging and anatomopathological diagnosis of focal liver lesions. Methods: a descriptive study was conducted in 60 patients with liver lesions diagnosed by ultrasound in the imaging center of the Dr. Gustavo Aldereguía Lima Hospital in Cienfuegos, from March 1st, 2011 to March 31st, 2012. The variables were: age, gender, skin color, reasons for conducting ultrasound, personal medical history, ultrasonographic features, topography and number of lesions and anatomopathological results. Results: the most affected patients were 40 to 59 years old, predominantly female (63.4 %) and white (70%). Echogenic and anechoic tumor images prevailed, especially in the right hepatic lobe. The most common cause for conducting ultrasound was abdominal pain. Benign lesions (63.3%) were noted, and the most frequently observed tumor was hemangioma. Liver metastases were more common than primary liver tumors. Conclusion: there was very a positive relationship between ultrasonographic and anatomopathological findings in focal liver lesions, showing differences between them and clinical presentations.